SELF-CONCEPT AND WIFE'S ASSERTIVENESS IN DEALING MARITAL CONFLICTS - Wiwik Juwarini Prihastiwi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The purpose of this study was to determine the role of self-concept, education level, and employment status on women's assertiveness in dealing with marital conflict. The subjects of this study were 101 wives taken using a multistage random sampling technique. The data in this study were taken with a scale arranged based on the Likert model. Hypothesis testing used correlation analysis and t-test. Product moment correlation analysis showed that there was a significant relationship between self-concept and assertiveness and there was a significant relationship between education and assertiveness. The results of other analyses, namely partial correlation analysis, showed that there was a significant relationship between education level and assertiveness by controlling for self- concept (r1.y-2 = 0.242; p = 0.015). The results of the partial correlation analysis showed a significant relationship between self-concept and assertiveness by controlling for education level (r2.y-1 = 0.312; p = 0.002. The results of the t-test showed no difference in wife's assertiveness in terms of employment status (p > 0.01). The contribution of the self-concept variable (8.187%) to assertiveness was higher than education level. (6.870).